Alternativna paradigma / Alternative paradigm - Karčić, Fikret (Context: Journal of Interdisciplinary Studies, 2022)
Wael B. Hallaq, The Impossible State: Islam, Politics and Modernity’s Moral Predicament (New York: Columbia University Press, 2013), str. 256.